find f(-2)=-x^2-4x-5

Thank you for the opportunity to help you with your question!

Given

f(x) = x^2 -4x -5

now to solve for f(-2) just plug x=-2 in f(x)

so we get

f(-2) = (-2)^2 - 4(-2) - 5

= 4 + 8 -5

= 7

the value of f(-2) = 7

comment for any doubts. rate as best . thank you

oh sorry i took f(x) wrong

f(x) = -x^2 -4x -5

f(-2) = - (-2)^2 -4(-2) -5

= -4 + 8 -5

= -9 +8

= -1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up